The Global Burden of Road Injury: Its Relevance to the Emergency Physician - Sharon Chekijian; Melinda Paul; Vanessa P. Kohl; David M. Walker; Anthony J. Tomassoni; David C. Cone; Federico E. Vaca (Emergency Medicine International)
Background. Road traffic crash fatalities in the United States are at the lowest level since 1950. The reduction in crash injury burden is attributed to several factors: public education and prevention programs, traffic safety policies and enforcement, improvements in vehicle design, and prehospital services coupled with emergency and acute trauma care. Globally, the disease burden of road traffic injuries is rising. In 1990, road traffic injuries ranked ninth in the ten leading causes of the global burden of disease. By 2030, estimates show that road traffic injuries will be the fifth leading causes of death in the world. Historically, emergency medicine has played a pivotal role in contributing to the success of the local, regional, and national traffic safety activities focused on crash and injury prevention. Objective. We report on the projected trend of the global burden of road traffic injuries and fatalities and describe ongoing global initiatives to reduce road traffic morbidity and mortality. Discussion. We present key domains where emergency medicine can contribute through international collaboration to address global road traffic-related morbidity and mortality. Conclusion. International collaborative programs and research offer important opportunities for emergency medicine physicians to make a meaningful impact on the global burden of disease.